Molecular Engineering of Copper Phthalocyanines: A Strategy in Developing Dopant‐Free Hole‐Transporting Materials for Efficient and Ambient‐Stable Perovskite Solar Cells. Issue 4 (5th December 2018) - Jiang, Xiaoqing; Wang, Dongping; Yu, Ze; Ma, Wanying; Li, Hai‐Bei; Yang, Xichuan; Liu, Feng; Hagfeldt, Anders; Sun, Licheng
Abstract: Copper (II) phthalocyanines (CuPcs) have attracted growing interest as promising hole‐transporting materials (HTMs) in perovskite solar cells (PSCs) due to their low‐cost and excellent stability. However, the most efficient PSCs using CuPc‐based HTMs reported thus far still rely on hygroscopic p‐type dopants, which notoriously deteriorate device stability. Herein, two new CuPc derivatives are designed, namely CuPc‐Bu and CuPc‐OBu, by molecular engineering of the non‐peripheral substituents of the Pc rings, and applied as dopant‐free HTMs in PSCs. Remarkably, a small structural change from butyl groups to butoxy groups in the substituents of the Pc rings significantly influences the molecular ordering and effectively improves the hole mobility and solar cell performance. As a consequence, PSCs based on dopant‐free CuPc‐OBu as HTMs deliver an impressive power conversion efficiency (PCE) of up to 17.6% under one sun illumination, which is considerably higher than that of devices with CuPc‐Bu (14.3%). Moreover, PSCs containing dopant‐free CuPc‐OBu HTMs show a markedly improved ambient stability when stored without encapsulation under ambient conditions with a relative humidity of 85% compared to devices containing doped Spiro‐OMeTAD. This work thus provides a fundamental strategy for the future design of cost‐effective and stable HTMs for PSCs and other optoelectronic devices. Abstract : Two new copper (II) phthalocyanine (CuPc) derivatives, namely CuPc‐Bu and CuPc‐OBu, are designed by molecular engineering of the non‐peripheral substituents of the Pc rings, and are further explored as dopant‐free hole‐transporting materials (HTMs) in perovskite solar cells (PSCs). The PSCs based on pristine CuPc‐OBu as HTMs afford a maximum power conversion efficiency of 17.6%, which is considerably higher than that of the devices with CuPc‐Bu (14.3%).